The Soul of Jesus in the Land of the Dead: Origen on the Harrowing of Hell - Rivera, Charles Augustine (Harvard theological review, 2025)
This article offers an account of Origen’s understanding of Jesus’s descent into Hades, drawing on the full breadth of his corpus. I argue that Origen develops two themes in his writing on the descent. First, the descent completes the defeat of the devil, which began when Jesus offered himself as a ransom for humankind. Second, Origen understands the descent into Hades as the final stage of the savior’s revelatory descent through all the different realms of the cosmos. In both cases Origen’s characteristic conception of the soul of Jesus plays an essential part. Thus, Origen argues that it is the perfect virtue of Jesus’s soul and not the divine power of the Son of God that destroys the devil’s power. Likewise, Origen’s understanding of a rational mind’s ability to take on different bodily forms underlies his idea of the savior’s descent through different realms of the cosmos.